Role of ethanol to water ratio in hydrogen production by ethanol steam reforming in atmospheric pressure 915 MHz microwave plasma - Robert Miotk; Bartosz Hrycak; Dariusz Czylkowski; Jerzy Mizeraczyk; Mirosław Dors; Mariusz Jasiński (Scientific Reports)
Abstract As interest in the hydrogen economy grows, the demand for efficient, cost-effective, and sustainable hydrogen production methods increases. In response, this work focuses on developing a small-scale hydrogen production method based on ethanol steam reforming in low-temperature microwave plasma. The process operates at 915 MHz under atmospheric pressure, offering a catalyst-free approach. Using a metal-cylinder-based nozzleless microwave plasma source, the study investigates how varying the ethanol-to-water ratio influences the efficiency of hydrogen generation. To evaluate this efficiency, gas chromatography and infrared spectrometry are used to measure the hydrogen production rate, energy yield, and hydrogen content, while optical emission spectroscopy offers insights into plasma parameters such as vibrational and rotational temperatures. The highest hydrogen production efficiency is achieved at the ethanol-to-water ratio of 3:1, with a hydrogen production rate of 149.8 g(H2)/h and an energy yield of 29.9 g(H2)/kWh. These findings highlight the potential of microwave plasma technology for distributed hydrogen production, offering an efficient and sustainable alternative to traditional large scale methods.